Proteomic characterization of human early pro-angiogenic cells - Urbich, Carmen; De Souza, Ayesha I; Rossig, Lothar; Yin, Xiaoke; Xing, Qiuru; Prokopi, Marianna; Drozdov, Ignat; Steiner, Marianne; Breuss, Johannes; Xu, Qingbo; Dimmeler, Stefanie; Mayr, Manuel (My University, 2011)
Early pro-angiogenic cells (EPCs) have been shown to be involved in neovascularization, angiogenesis and re-endothelialization and cathepsin L inhibition blunted their pro-angiogenic effect. In the present study, we have analysed and mapped the proteome and secretome of human EPCs, utilizing a combination of difference in-gel electrophoresis (DIGE) and shotgun proteomics. A population of 206 protein spots were analysed, with 171 being identified in the cellular proteome of EPCs. 82 proteins were identified in their conditioned medium, including the alternative macrophage markers C-C motif chemokine 18 (CCL18) and the hemoglobin scavenger receptor CD163 as well as platelet factor 4 (CXCL4) and platelet basic protein (CXCL7) with "platelet alpha granule" being returned as the top category according to the Gene Ontology Annotation. Apart from cathepsin L, the cathepsin L inhibitor also attenuated the release of a wide range of other cathepsins and lysosomal proteins such as legumain, but stimulated the secretion of members of the S100 protein family. The data presented here are the most comprehensive characterization of protein expression and secretion in human EPCs to date and highlight the potential importance of cysteine proteases in the processing of platelet factors for their pro-angiogenic potential. This article is part of a special issue entitled, "Cardiovascular Stem Cells Revisited".
Keywords: Angiogenesis; Cell therapy; Endothelium; Monocytes; Platelets; Proteomics